Can we identify subfertile couples that benefit from immediate in vitro fertilisation over intrauterine insemination?. (July 2016) - Tjon-Kon-Fat, Raïssa I.; Tajik, Parvin; Custers, Inge M.; Bossuyt, Patrick M.M.; van der Veen, Fulco; van Wely, Madelon; Mol, Ben W.; Zafarmand, Mohammad H.
Abstract: Objective: Available treatment options in couples with unexplained or mild male subfertility are intrauterine insemination with controlled ovarian hyperstimulation (IUI-COH) and in vitro fertilisation (IVF). IUI-COH is a less invasive treatment that is often used before proceeding with IVF. Yet as the IVF success rates might be higher and time to pregnancy shorter, expedited access to IVF might be the preferred option. To identify couples that could benefit from immediate IVF over IUI-COH, we assessed whether female age, duration of subfertility or prewash total motile count (TMC) can help to identify couples that would benefit from IVF over IUI-COH. Study design: We performed a secondary data-analysis of a multicentre open-label randomised controlled trial in three university and six teaching hospitals in the Netherlands. 116 couples with unexplained or mild male subfertility were randomised to one cycle of IVF with elective single embryo transfer with subsequent frozen-thawed embryo transfers or 3 cycles of IUI-COH. The primary outcome was an ongoing pregnancy within 4 months after randomisation. Our aim was to explore a possible differential effect of specific markers on the effectiveness of treatment. We chose to therefore assess female age, duration of subfertility and TMC as these have previously been identified as predictors. For each prognostic factor we developed a logistic regression model to predict ongoing pregnancy with that prognostic factor, treatment and a factor-by-treatment interaction term. Results: Female age and duration of subfertility were not associated with better ongoing pregnancy chances after IVF compared to IUI-COH ( p -value for interaction = 0.65 and 0.26, respectively). Only when TMC was lower than 110 (×10 6 spermatozoa/mL), the probability of ongoing pregnancy was higher in women allocated to IVF ( p -value for interaction = 0.06). Conclusion: In couples with unexplained or mild male subfertility, a low TMC might lead to higher pregnancy rates after IVF than after IUI-COH. This finding needs to be validated in a larger trial before it can be applied in clinical practice.